Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas Pada CSR Disclosure - Dewi, Ni Komang Ayu Trisna; Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi; Vol 27 No 3 (2019)DO - 10.24843/EJA.2019.v27.i03.p12, 2019)
This study aims to determine the effect of company size, leverage, and profitability on CSR disclosure. The theory used in this study is stakeholder theory and legitimacy theory. The research sample was 29 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2017 with a purposive sampling method. The analysis technique used is the Analysis of Multiple Linear Regression. The results showed that (1) the size of the company has a positive effect on CSR disclosure which shows that the greater the size of the company, the CSR disclosure policy will be more widespread. (2) leverage does not affect CSR disclosure which shows that a company's leverage ratio does not affect disclosure CSR, (3) Profitability shows that the greater the company's profitability, the company is obliged to disclose CSR Keywords : CSR, company size, leverage, profitability